Microbial Ecology of Aerial Plant Surfaces - Bailey, M.J (CABI, 2014)
The field of phyllosphere microbiology is a large one, encompassing such diverse topics as the chemical and physical environment of a diversity of different types of plant surfaces, a description of a wide diversity of inhabitants of plant surfaces, the interactions that such organisms have with the plant and with each other, as well as many other related topics. Because the field is so broad, it is impossible for any one overview to be comprehensive. Furthermore, the biases of the author will certainly dictate the emphasis on certain topics. In that respect, this overview will also reveal the biases of this author. It will thus be somewhat bacterial-centric given both the predominant experiences of this author with this group of organisms as well as the prominence of bacterial studies at the expense of the studies of other microbial groups. Several excellent reviews of the microbiology of the phyllosphere or related topics have appeared in recent years (Beattie and Lindow, 1995; Jacques and Morris, 1995; Kinkel, 1997; Johnson and Stockwell, 1998; Beattie and Lindow, 1999; Andrews and Harris, 2000; Hirano and Upper, 2000; Lindow and Leveau, 2002; Lindow and Brandl, 2003) in which more detailed discussions of various aspects of phyllosphere microbiology are provided.